Parenting styles and hyperactivity among primary school students - عزيز, عمر ابراهيم; الله, فرمان زهر عبد (Sulaimani Journal for Humanities, 2019)
Parenting Styles and Hyperactivity Disorder Among Basic School Stage Pupils Hyperactivity Disorder is the most common disorders in the institutes of mental health and pediatrics. Studies show the opposite of the early beliefs that this disorder disappears as soon as the child becomes an adolescent. Researchers suggest that the patient’s family, specifically the problems related to the personality of the parents and their parenting styles lead to their children infection with different disorders including hyperactivity disorder. Yet results of previous studies show that there is a contrasting effect, as well as different, concerning this disorder across cultures which calls for more study. Thus the aims of the research determined as follows: 1. Knowing the rates of prevalence of hyperactivity disorder among basic school stage pupils of teenagers in the morning governmental schools in Sulaimani Governorate. 2. Identifying the common styles of parenting among basic school stage pupils of teenagers in the morning governmental schools in Sulaimani Governorate. 3. Identifying the extent of contribution of each style of parenting in evoking hyperactivity disorder in basic school stage pupils of teenagers in the morning governmental schools in Sulaimani Governorate. The results indicated that prevalent rate of hyperactivity was (18%) according to a parent’s questionnaire (male of 10% and female of 8%). Whereas according to a teachers’ questionnaire it was (19%) (male of 13% and female of 6%), and parents’ using of positive styles in treating their children like involvement and positive parenting more than using negative styles like poor monitoring, inconsistency, and corporal punishment. Both poor monitoring and corporal punishment interpreted (3.7%) of the variance in the degrees of hyperactivity (parent’s questionnaire), and poor monitoring was a better predictor than the other, which interpreted (2.6%) of the variance in the degrees of hyperactivity, while corporal punishment interpreted only (1.1%). In teachers’ questionnaire, poor monitoring was the only predictor among the rest of the styles which interpreted (4.5%) of the variance in the degrees of hyperactivity disorder.